An Analysis of Nigerian TVET Graduates’ Career Decision Self-Efficacy - Otu, Mkpoikanke; Sefotho, Maximus Monaheng (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study examined the degree of career decision self efficacy among recent graduates of technical vocational education and training in Nigeria. The aim was to understand how these graduates perceive their ability to make informed career choices, and to determine whether demographic characteristics predict their levels of self efficacy. Methods and Materials: The study employed a quantitative survey design involving three hundred and fifty recent graduates from the southeast region of Nigeria. A purposive sampling approach ensured representation across different technical vocational education programs, genders, ages and marital statuses. Data were gathered using the Career Decision Self Efficacy Scale Short Form, which contains twenty five items rated on a five point Likert scale. Regression analysis was used to examine the predictive influence of demographic variables. Findings: The results indicated that graduates displayed a high level of career decision self efficacy. The regression model showed that demographic characteristics significantly predicted self efficacy outcomes. Graduates with stronger academic achievement and those enrolled in more relevant technical vocational education programs reported higher levels of self efficacy. Conclusion: The findings highlight the need for policymakers, counsellors and educators to strengthen targeted interventions that support career planning and transition for technical vocational education graduates. Enhanced guidance programmes may further improve graduates’ confidence and readiness for labour market entry. This study provides empirical insight into the career decision competence of technical vocational education graduates in Nigeria, contributing evidence that can inform national strategies for improving career development support within the sector.